Systematic review of analgesics and dexamethasone for post-tonsillectomy pain in adults - Tolska, H.K.; Hamunen, K.; Takala, A.; Kontinen, V.K. (British journal of anaesthesia : BJA, 2019)
Intense pain can last several days after tonsillectomy. It is often undertreated and improved analgesic strategies that can be safely used at home are needed. We conducted a systematic review and meta-analysis on the effectiveness of systemic medications used for post-tonsillectomy pain in adult and adolescent (13 yr old) patients. Studies were identified from PubMed, the Cochrane Library, and by hand searching reference lists from studies and review articles. Randomised, double-blind, placebo-controlled studies reporting on pain intensity or use of rescue analgesia were included. Twenty-nine randomised controlled trials representing 1816 subjects met the inclusion criteria. Follow-up time was ≤24 h in 15 studies, in which the majority were taking nonsteroidal anti-inflammatory drugs. Thirteen studies were suitable for meta-analysis. In pooled analysis, paracetamol, dexamethasone, and gabapentinoids reduced pain intensity on the day of operation. In individual studies, ketoprofen, ibuprofen, lornoxicam, parecoxib, rofecoxib, indomethacin and dextromethorphan reduced pain intensity, need for rescue analgesics, or both on the day of operation. Oral celecoxib for 2 postoperative weeks or i.v. ketamine on the day of operation were not effective at the studied doses. Dexamethasone in multiple doses provided analgesia beyond 1 postoperative day. Pain was moderate to strong in both study and control groups during the first postoperative week. Single analgesics and dexamethasone provide only a weak to moderate effect for post-tonsillectomy pain on the day of operation and thus a multimodal analgesic strategy is recommended. Short follow-up times and clinical heterogeneity of studies limit the usefulness of results.